Feminism in ‘The Dark Holds No Terror’ By Shashi Deshpande: Exploring Psychological Issues in Shashi Deshpande's 'The Dark Holds No Terror' (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Woman is neither organically nor mentally sub-par compared to man yet traditionally, in human progress, she has been dealt with mediocre compared to man. She has been given the optional status in the general public and isn't perceived as a human with a personality. 'Feminism', the counter man controlled society development emerges and contemplates the women issues in this way making mindfulness. Activities which incorporate feminist writing among others which look to free women from the subjection and misuse of man and to develop and libertarian culture can be back dated to the 1960s. Sashi Despande, an unmistakable feminist writer whose novel 'The Dark Holds No Terrors' is analyzed. The goal of this paper depicts the psychological issues that a career arranged woman experiences in her day to day existence. The emergency is a result of the darkness that continues in one's psyche. One must emerge from this terror and face the issues strongly with fearlessness. Approaches, for example, Simon De Beauvoir analysis is embraced in gathering the targets. The exploration will be done in the point of view of feminist hypothesis of Simon De Beauvoir's The Second Sex.